Annual maximum 5-day rainfall total and maximum number of consecutive dry days over Central America and the Caribbean in the late twenty-first century projected by an atmospheric general circulation model with three different horizontal resolutions - T. Nakaegawa; A. Kitoh; H. Murakami; S. Kusunoki (Theoretical and Applied Climatology, 2014)

Caribbean low‐level jets and accompanying moisture fluxes in a global warming climate projected with CMIP3 multi‐model ensemble and fine‐mesh atmospheric general circulation models - T. Nakaegawa; A. Kitoh; Y. Ishizaki; S. Kusunoki; H. Murakami (International Journal of Climatology, 2014)
This study used the third phase of the Coupled Model Intercomparison Project ( CMIP3 ) multi‐model ensemble ( MME ) and atmospheric general circulation models ( AGCMs ) with three horizontal resolutions, 20, 60, and 180 km, to investigate climate projections of the Caribbean low‐level jet ( CLLJ ) and accompanying moisture fluxes. Future climate simulations were also performed with 60‐ and 180‐km mesh AGCMs forced by four lower boundary conditions both to quantify uncertainty in the CLLJ projections and to determine the physical mechanism of change in the CLLJ . Changes among the CMIP3 MME models in projected CLLJ in the future climate were inconsistent in sign and statistically insignificant, whereas consistently among the models the easterly moisture flux accompanying the CLLJ significantly intensified. The AGCM simulations with three different horizontal resolutions demonstrated that the merits of dynamical downscaling for the CLLJ and moisture flux were limited for climate projections, although the high‐horizontal resolution models improved reproducibility of the CLLJ and moisture flux in the present‐day climate and can provide spatially detailed projections. Different projected sea surface temperatures ( SST s) as lower boundary conditions of the 60‐ and 180‐km mesh single‐ AGCM simulations clearly affected changes in the CLLJ . Both the CMIP3 MME analysis and the 60‐ and 180‐km mesh AGCM ensembles showed that large‐scale SST patterns between the eastern tropical Pacific and the region from the Caribbean Sea to the western tropical Atlantic influenced changes in the CLLJ in the future climate, as seen in the present‐day climate.

The Asian summer monsoon: an intercomparison of CMIP5 vs. CMIP3 simulations of the late 20th century - K. R. Sperber; H. Annamalai; I.-S. Kang; A. Kitoh; A. Moise; A. Turner; B. Wang; T. Zhou (Climate Dynamics, 2013)

Future climate of the Caribbean from a super-high-resolution atmospheric general circulation model - Trevor C. Hall; Andrea M. Sealy; Tannecia S. Stephenson; Shoji Kusunoki; Michael A. Taylor; A. Anthony Chen; Akio Kitoh (Theoretical and Applied Climatology, 2013)

Will the South Asian monsoon overturning circulation stabilize any further? - R. Krishnan; T. P. Sabin; D. C. Ayantika; A. Kitoh; M. Sugi; H. Murakami; A. G. Turner; J. M. Slingo; K. Rajendran (Climate Dynamics, 2013)

Monsoon circulation interaction with Western Ghats orography under changing climate - K. Rajendran; A. Kitoh; J. Srinivasan; R. Mizuta; R. Krishnan (Theoretical and Applied Climatology, 2012)

Evaluation of coupled ocean–atmosphere simulations of the mid-Holocene using palaeovegetation data from the northern hemisphere extratropics - J. Wohlfahrt; S. P. Harrison; P. Braconnot; C. D. Hewitt; A. Kitoh; U. Mikolajewicz; B. L. Otto-Bliesner; S. L. Weber (Climate Dynamics, 2008)

Past and future polar amplification of climate change: climate model intercomparisons and ice-core constraints - V. Masson-Delmotte; M. Kageyama; P. Braconnot; S. Charbit; G. Krinner; C. Ritz; E. Guilyardi; J. Jouzel; A. Abe-Ouchi; M. Crucifix; R. M. Gladstone; C. D. Hewitt; et al. (Climate Dynamics, 2006)

Past and future polar amplification of climate change: climate model intercomparisons and ice-core constraints - V. Masson-Delmotte; M. Kageyama; P. Braconnot; S. Charbit; G. Krinner; C. Ritz; E. Guilyardi; J. Jouzel; A. Abe-Ouchi; M. Crucifix; R. M. Gladstone; C. D. Hewitt; et al. (Climate Dynamics, 2006)

A multi-model analysis of the role of the ocean on the African and Indian monsoon during the mid-Holocene - Y. Zhao; P. Braconnot; O. Marti; S.P. Harrison; C. Hewitt; A. Kitoh; Z. Liu; U. Mikolajewicz; B. Otto-Bliesner; S.L. Weber (Climate Dynamics, 2005)

AGCM simulations of intraseasonal variability associated with the Asian summer monsoon - D. E. Waliser; K. Jin; I.-S. Kang; W. F. Stern; S. D. Schubert; M. L. C. Wu; K.-M. Lau; M.-I. Lee; V. Krishnamurthy; A. Kitoh; G. A. Meehl; V. Y. Galin; et al. (Climate Dynamics, 2003)

Intercomparison of the climatological variations of Asian summer monsoon precipitation simulated by 10 GCMs - Kang I.-S.; Jin K.; Wang B.; Lau K.-M.; Shukla J.; Krishnamurthy V.; Schubert S.; Wailser D.; Stern W.; Kitoh A.; Meehl G.; Kanamitsu M.; et al. (Climate Dynamics, 2002)

STOIC: a study of coupled model climatology and variability in tropical ocean regions - Davey M.; Huddleston M.; Sperber K.; Braconnot P.; Bryan F.; Chen D.; Colman R.; Cooper C.; Cubasch U.; Delecluse P.; DeWitt D.; Fairhead L.; et al. (Climate Dynamics, 2002)

ENSIP: the El Niño simulation intercomparison project - M. Latif; K. Sperber; J. Arblaster; P. Braconnot; D. Chen; A. Colman; U. Cubasch; C. Cooper; P. Delecluse; D. Dewitt; L. Fairhead; G. Flato; et al. (Climate Dynamics, 2001)

Northern Hemisphere atmospheric blocking as simulated by 15 atmospheric general circulation models in the period 1979-1988 - F. D'Andrea; S. Tibaldi; M. Blackburn; G. Boer; M. Déqué; M. R. Dix; B. Dugas; L. Ferranti; T. Iwasaki; A. Kitoh; V. Pope; D. Randall; et al. (Climate Dynamics, 1998)

East Asian winter monsoon: results from eight AMIP models - Y. Zhang; K. R. Sperber; J. S. Boyle; M. Dix; L. Ferranti; A. Kitoh; K. M. Lau; K. Miyakoda; D. Randall; L. Takacs; R. Wetherald (Climate Dynamics, 1997)